The women’s advocacy school: Strengthening gender-responsive legal literacy and networking in Baubau City - Satria, Eko; Nur, Al Hiday (Community Empowerment, 2025)
The limited capacity for gender-perspective legal advocacy among young women activists hinders the struggle for women's rights at the local level. The "Women’s Advocacy School" program in Baubau City aims to strengthen legal literacy, advocacy techniques, and collaborative cross-organizational networking. Employing a participatory community development approach, the program included intensive training focused on women’s legal standing, issue analysis, and public communication. The results demonstrated a significant increase in participants' conceptual understanding and self-confidence. Participation dynamics improved markedly, evidenced by critical interactions in forums, with 27% of participants actively engaging as inquisitors and 7% as reflective respondents to complex issues. This success confirms that structured advocacy education models can effectively transform young activists into competent agents of change. The program recommends sustained institutional support to replicate this model and broaden the impact of gender advocacy regionally.